2014
DOI: 10.11646/zootaxa.3895.1.5
|View full text |Cite
|
Sign up to set email alerts
|

A missing geographic link in the distribution of the genus Echinotriton (Caudata: Salamandridae) with description of a new species from southern China

Abstract: Disjunct geographic distribution of a species or a group of species is the product of long-term interaction between organisms and the environment. Filling the distributional gap by discovery of a new population or a species has significant biogeographic implications, because it suggests a much wider past distribution and provides evidence for the route of range expansion/contraction. The salamandrid genus Echinotriton (commonly known as spiny salamanders, spiny newts, or crocodile newts) has two species that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 28 publications
(1 reference statement)
0
15
0
Order By: Relevance
“…They highlighted Goniurosaurus species as taxa likely to become commercial commodities, and called for caution in disclosing exact localities in describing new species. Hou et al (2014) also reported similar cases of poaching on restricted-range herpetofauna for the pet market following disclosure of locality information in formal publications.…”
Section: Discussionmentioning
confidence: 83%
“…They highlighted Goniurosaurus species as taxa likely to become commercial commodities, and called for caution in disclosing exact localities in describing new species. Hou et al (2014) also reported similar cases of poaching on restricted-range herpetofauna for the pet market following disclosure of locality information in formal publications.…”
Section: Discussionmentioning
confidence: 83%
“…Two East Asian newt species have already been extirpated in all or a significant part of their ranges (Lau et al, 2007), and at least one Southeast Asian newt is perilously close to being driven to extinction in the wild primarily due to the pet trade (Stuart et al, 2014). The threat of the illegal pet trade to Asian newts is such that a recent publication describing a new newt species from China, Echinotriton maxiquadratus, did not reveal the collection locality and made the specific request that "all hobbyists…refrain themselves from collecting this salamander or leaking locality information if encountered, and boycott any trading" (Hou et al, 2014;pp 89. ).…”
Section: Discussionmentioning
confidence: 99%
“…Some sources [ 4 , 15 , 29 ] termed the large, sculptured bone that is in broad contact with the posterior end of the maxilla in Chelotriton the quadratojugal, whereas [ 22 ] interpreted this bone in the same taxon as the quadrate. A bone in a comparable position was referred to as the quadrate in Tylototriton and Echinotriton [ 8 , 33 , 45 ], and a separate quadratojugal bone was described neither in these nor in other pleurodelines. In most anatomical studies dealing with the salamander skull, a quadratojugal bone is not identified.…”
Section: Methodsmentioning
confidence: 99%
“…A rather smooth, triangular piece of bone in the right orbitotemporal fenestra (Figs 8 and 11 ) is connected posteromedially to a fragment of a thicker bone. This could represent the ventromedial process of the maxilla that was sutured to the pterygoid, as in Tylototriton [ 22 ] or Echinotriton [ 8 , 45 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation